Resource sharing across heterogenous networks - Hazelhurst, Scott Edward (My University, 2015)
Sharing resources on a computer network, especially in heterogeneous environments, has m any benefits: new applications become possible, and use of technology cheaper. This dissertation investigates how resources— in particular printing resources—may b e shared. While still incomplete, an existing theoretical framework for data communication and resource sharing, the ISO-051 Reference Model, provides useful background information and tools for analysis. A discussion o f this framework complements a survey o f the principles and current state of file and printer servers, and distributed systems. An analysis of the design and implementation of a printer server acting as a b ridge between two networks illustrates problem s and results found in distributed system s generally. The dissertation concludes by analyzing the strengths and shortcomings of the Reference Model and distributed systems. This and developments in technology lead to a proposal of an extended model for printer services, and clarification of printer servers' needs and requirements.